Development of 3D Digital-Based Teaching Materials with Augmented Reality Technology In Improving Early Childhood Literacy Skills - Salpina Salpina; Maisura Maisura; Dwi Adhinda Junaidi Putri; Faizah M. Nur (Edumaspul: Jurnal Pendidikan, 2024)
The urgency of this research is the need to improve the literacy skills of early childhood which are increasingly decreasing, because literacy is very important for children, namely as a means of developing language and communication. Furthermore, literacy allows children to access and understand knowledge from various sources. The development of children's literacy skills should develop along with the times, this encourages the use of technology as an open material to improve the literacy skills of early childhood. Teachers as educators play an important role in the technology-integrated learning process. Teachers must have competence in integrating technology in the learning process. Therefore, researchers provide a solution to all teachers by developing 3D Digital-based teaching materials with Augmented Reality (AR) technology. The aim of this research is to increase children's literacy interest. The method in this research uses a four-D plan, in this plan there are four stages, namely: (1). Defining stage, (2). Design Stage (3). Developing stage (4). Socialization stage. The research results obtained with technology will make learning more optimal and creative so that it can stimulate the development of power, creativity and language.